Teacher competencies of teacher a medical career of the University of El Salvador - Rosa María Esteban Moreno; Ana María Laínez Cañas; Sara Menjívar de Barbón; Sonia Monroy Flores; Vilma Quan Martínez (Universitat Politècnica de València, 2012)
This article highlights the results of the Faculty of Medicine of the University of El Salvador, as part of an international joint research between the University Autonoma de Madrid and Central American public universities, whose development has taken more than three years of work. The research, which has been funded with support from the Spanish Agency for International Development Cooperation (AECI) and the collaboration of the participating universities, has identified the teaching skills of teachers of the medical course in Central America to develop a teacher training project to strengthen the professionalism of teachers in the educational process. To develop the study used a mix quantitative and qualitative methodological and triangulation results, using questionnaires, interviews, focus groups and life histories, which have extraordinarily enriched the study, allowing protagonists of higher education teachers and students, speak in first person about his personal experience of teaching competencies, their strengths and weaknesses. According to quantitative data, evaluated teachers dominate the teaching competencies investigated, but qualitative analysis shows contradictions on the dominance of some of the competencies by teachers, concluding on the need to further develop training processes that favor teacher training in order to contribute in improving the quality of university education.